2017
DOI: 10.1155/2017/7163198
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal N400 Semantic Priming Effect May Reflect Psychopathological Processes in Schizophrenia: A Twin Study

Abstract: Objective Activation of semantic networks is indexed by the N400 effect. We used a twin study design to investigate whether N400 effect abnormalities reflect genetic/trait liability or are related to psychopathological processes in schizophrenia. Methods We employed robust linear regression to compare N400 and behavioral priming effects across 36 monozygotic twin pairs (6 pairs concordant for schizophrenia/schizoaffective disorder, 11 discordant pairs, and 19 healthy control pairs) performing a lexical decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Previous studies have consistently found that patients with psychosis showed reduced N400 amplitude to semantically incongruent words compared to controls, as well as smaller priming effects (difference between N400 amplitude to congruent and incongruent words) [119,120]. Similar deficits in N400 were also found in individuals at clinical high risk [121], but not in unaffected relatives of patients [122,123], indicating that N400 might be a state marker for psychosis instead of an endophenotype of genetic predisposition.…”
Section: N400mentioning
confidence: 77%
“…Previous studies have consistently found that patients with psychosis showed reduced N400 amplitude to semantically incongruent words compared to controls, as well as smaller priming effects (difference between N400 amplitude to congruent and incongruent words) [119,120]. Similar deficits in N400 were also found in individuals at clinical high risk [121], but not in unaffected relatives of patients [122,123], indicating that N400 might be a state marker for psychosis instead of an endophenotype of genetic predisposition.…”
Section: N400mentioning
confidence: 77%
“…For instance, antipsychotic treatment is associated with improvement in N400 semantic priming deficits in patients with schizophrenia (Besche-Richard, Iakimova, Hardy-Bayle, & Passerieux, 2014;Condray et al, 2003;Condray, Steinhauer, Cohen, van Kammen, & Kasparek, 1999;Goldberg, Dodge, Aloia, Egan, & Weinberger, 2000). Moreover, N400 semantic priming effects were found to be normal in schizophrenia patients' first-degree relatives, including monozygotic twins (Kiang et al, 2014;Sharma et al, 2017), providing convergent evidence that N400 priming deficits are a biomarker of the psychotic state itself rather than of genetic risk for developing schizophrenia.…”
Section: Introductionmentioning
confidence: 98%
“…A major confounding factor is the use of word semantics during the task. Presented deficits may not reflect spatial (somatic) representation of words, but aberrant semantic networks are evidenced for patients with psychosis ( 36 ) and semantic priming effect ( 37 ). This effect enables faster decision-making due to presentation with context information, hence in our study, preceding words could induce choosing the other one as the next in the procedure of placing.…”
Section: Discussionmentioning
confidence: 96%